Mouse models of lung-specific SARS-CoV-2 infection with moderate pathological traits - Kim, Sung-Hee; Kim, Jiseon; Jang, Ji Yun; Noh, Hyuna; Park, Jisun; Jeong, Haengdueng; Jeon, Donghun; Uhm, Chanyang; Oh, Heeju; Cho, Kyungrae; Jeon, Yoon; On, Dain; et al. (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) has been a global health concern since 2019. The viral spike protein infects the host by binding to angiotensin-converting enzyme 2 (ACE2) expressed on the cell surface, which is then processed by type II transmembrane serine protease. However, ACE2 does not react to SARS-CoV-2 in inbred wild-type mice, which poses a challenge for preclinical research with animal models, necessitating a human ACE2 (hACE2)-expressing transgenic mouse model. Cytokeratin 18 (K18) promoter-derived hACE2 transgenic mice [B6.Cg-Tg(K18-ACE2)2Prlmn/J] are widely used for research on SARS-CoV-1, MERS-CoV, and SARS-CoV-2. However, SARS-CoV-2 infection is lethal at ≥105 PFU and SARS-CoV-2 target cells are limited to type-1 alveolar pneumocytes in K18-hACE2 mice, making this model incompatible with infections in the human lung. Hence, we developed lung-specific SARS-CoV-2 infection mouse models with surfactant protein B (SFTPB) and secretoglobin family 1a member 1 (Scgb1a1) promoters. After inoculation of 105 PFU of SARS-CoV-2 to the K18-hACE2, SFTPB-hACE2, and SCGB1A1-hACE2 models, the peak viral titer was detected at 2 days post-infection and then gradually decreased. In K18-hACE2 mice, the body temperature decreased by approximately 10 °C, body weight decreased by over 20%, and the survival rate was reduced. However, SFTPB-hACE2 and SCGB1A1-hACE2 mice showed minimal clinical signs after infection. The virus targeted type I pneumocytes in K18-hACE2 mice; type II pneumocytes in SFTPB-hACE2 mice; and club, goblet, and ciliated cells in SCGB1A1-hACE2 mice. A time-dependent increase in severe lung lesions was detected in K18-hACE2 mice, whereas mild lesions developed in SFTPB-hACE2 and SCGB1A1-hACE2 mice. Spleen, small intestine, and brain lesions developed in K18-hACE2 mice but not in SFTPB-hACE2 and SCGB1A1-hACE2 mice. These newly developed SFTPB-hACE2 and SCGB1A1-hACE2 mice should prove useful to expand research on hACE2-mediated respiratory viruses.